Leveraging Digital Marketing for Sustainable Fundraising in Zakat Institutions: A Case of Badan Amil Zakat Nasional (BAZNAS) Yogyakarta City - Kancana, Sauptika; Zaki, Ahmad; Santosa, Budi; Utomo, Hastho Joko Nur (RSF Conference Series: Business, Management and Social Sciences, 2025)
Zakat institutions play a pivotal role in fostering socio-economic equity; however, their fundraising potential remains underutilized in Indonesia, where only a fraction of the estimated zakat potential is actually collected. Previous studies highlight the promise of digital transformation; however, limited research has explored its systematic application in enhancing sustainable fundraising. This study examines how the National Zakat Agency (BAZNAS) Yogyakarta leverages digital marketing strategies to strengthen zakat collection and management. The research adopts a qualitative case study approach, employing literature review, document analysis, and semi-structured interviews with five key stakeholders: the Chairman of BAZNAS Yogyakarta, the Deputy Chairman IV, the Head of the IT Team, the Person-in-Charge of Division 1, and the Person-in-Charge of Division 2. Findings reveal that BAZNAS Yogyakarta strategically utilizes social media campaigns, particularly Instagram, along with website optimization and fintech integration to broaden outreach and simplify zakat transactions. Transparency and accountability are reinforced through digital reporting systems such as the SIMBA application, which has significantly improved public trust and donor retention. Furthermore, the application of Islamic marketing principles and zakat literacy programs enhances engagement, particularly among millennials, who represent a critical donor segment. Despite notable progress, challenges persist, including digital literacy gaps and cybersecurity risks that require continuous innovation and investment. This study contributes to the literature on Islamic philanthropy by demonstrating the role of digital marketing in bridging the gap between zakat potential and realization, offering practical insights for zakat institutions seeking sustainable fundraising models.